Mean-field semantics for a process Calculus for spatially-explicit ecological models (2016)
ABSTRACT: We define a mean-field semantics for S-PALPS, a process calculus for spatially-explicit, individual- based modeling of ecological systems. The new semantics of S-PALPS allows an interpretation of the average behavior of a system as a set of recurrence equations. Recurrence equations are a useful approximation when dealing with a large number of individuals, as it is the case in epidemiological studies. As a case study, we compute a set of recurrence equations capturing the dynamics of an individual-based model of the transmission of dengue in Bello (Antioquia), Colombia.